2006
DOI: 10.1136/vr.158.3.81
|View full text |Cite
|
Sign up to set email alerts
|

Results of allergen‐specific immunotherapy in 117 dogs with atopic dermatitis

Abstract: The success of the treatment of 117 dogs with atopic dermatitis with allergen-specific immunotherapy for up to 48 months was assessed. An excellent response (remission with exclusive immunotherapy) was recorded in 18 of the dogs, a good response (more than 50 per cent reduction in medication and improvement of clinical signs) was recorded in 57, a moderate response was recorded in 24 and a poor response in 18. The mould antigens in the allergen extract were stored in a separate vial before administration and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 14 publications
(8 reference statements)
4
49
1
9
Order By: Relevance
“…Similar rates have been reported in studies evaluating AIT effectiveness [5, 1517, 19, 20]. Therapeutic extracts are likely to be imperfectly matched with dogs’ actual sensitivity with both AIT and RESPIT, perhaps accounting for the similarity in response rates.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar rates have been reported in studies evaluating AIT effectiveness [5, 1517, 19, 20]. Therapeutic extracts are likely to be imperfectly matched with dogs’ actual sensitivity with both AIT and RESPIT, perhaps accounting for the similarity in response rates.…”
Section: Discussionsupporting
confidence: 66%
“…On the basis of the changes in the dogs’ PVAS, LSI, and those concomitant systemic medications with substantial evidence of efficacy (glucocorticoids, cyclosporine, or oclacitinib) between D0 and D270+, an overall assessment score was assigned by the primary investigator as follows: 1 (poor) = no clinical change or a deterioration, 2 (fair) = improvement, but concurrent medications could not be substantially decreased, 3 (good) = greater than 50% improvement in clinical signs and reduction in medications, 4 (excellent) = complete remission without concurrent medications [17]. The percentages of dogs with D270+ PVAS in the normal (<2.0) and mild (2.0–3.5) ranges were determined.…”
Section: Methodsmentioning
confidence: 99%
“…It may take quite long for clinical signs to improve with AIT (Griffin and Hillier 2001, Loewenstein and Mueller 2009). In a retrospective study about AIT, 21 per cent of the dogs showed first signs of clinical improvement in the first two months of AIT, 45 per cent in the period between two months and five months, and 17 per cent of dogs later than five months (Schnabl and others 2006). Unfortunately, only an overall assessment of the owner was given and pruritus and CADESI scores were not obtained in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Allergen avoidance is the logical way to manage CAD, 6 but as this is frequently impractical or ineffective, alternative management regimes are often necessary. These include allergen‐specific immunotherapy (ASIT), 7–9 glucocorticoids, 10 ciclosporin, 11–15 antihistamines, 16–18 essential fatty acids 19–25 and Chinese herbal products 26,27 employed alone or in combination. The use of other anti‐inflammatory drugs such as pentoxifylline, 28 the prostaglandin E 1 (PGE 1 ) analogue misoprostol and leucotriene inhibitors, 29–32 recombinant interferon‐gamma 33 and topical treatments such as capsaicin 34 and tacrolimus 35 has also been reported.…”
Section: Introductionmentioning
confidence: 99%